Risk Diversification in the Credit Portfolio : An Overview of Country Practices - Morris, JoAnne (IMF Working Papers; Working Paper ;, 2001)
This paper reviews the rules in place in selected countries to limit risk concentrations in the credit portfolio. The paper focuses on a number of issues suggested by international organizations for countries and bank supervisors to consider in imposing standards for risk diversification in the credit portfolio. The issues reviewed for each country are the large exposure limits, the definition of credit exposure (including application on a consolidated basis), and the definition of a group of related borrowers. The paper concludes that most of the countries reviewed set limits on large exposures for banks and define a related group of borrowers in line with recommended international standards. The major differences identified among countries include how to determine the credit exposure, the application of the exposure limits on a consolidated basis, and whether to impose limits on exposure to a specific sector.